Legal Protection of Children Victims of Sexual Violence in the Family : Study of Decision Number 2068/Pid.Sus/2020/PN. Medan - Putriani Ndruru; Rahmayanti Rahmayanti; Ismaidar Ismaidar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Sexual violence within the family is a serious criminal act that not only violates the law but also causes profound physical and psychological suffering for victims. The complexity of such cases increases as the perpetrators are often close family members, resulting in trauma and obstacles in law enforcement. Decision Number 2068/Pid.Sus/2020/PN.Medan serves as the basis for analyzing the extent to which legal protection can be provided to victims. The research problems addressed are: (1) what forms of legal protection are available for victims of sexual violence within the family under Indonesian positive law, and (2) how such protection is implemented in Decision Number 2068/Pid.Sus/2020/PN.Medan. The research method applied is normative juridical with statutory, conceptual, and case study approaches. Data sources include legislation, legal literature, and court decision analysis. The findings reveal that legal protection for victims is regulated under the Child Protection Law, the Criminal Code, and other legal instruments emphasizing preventive, repressive, and rehabilitative measures. The Medan District Court imposed a severe sentence on the perpetrator in accordance with the law; however, protection for victims remains limited to formal aspects without comprehensive psychological recovery programs. In conclusion, the protection of victims of sexual violence within the family has been clearly regulated on a normative basis, but its implementation remains weak. Greater collaboration between law enforcement authorities, child protection institutions, and professionals is necessary to ensure the holistic recovery of victims.